Reliability of the digital functionally generated path technique for assessing occlusal interferences and adjusting CAD-CAM zirconia crowns: an in vivo study - Sherine Anwar Saad; Yousreya Atteya Shalaby; Amir Shoukry Azer (BMC, 2024)
Abstract Background Designing the occlusal surface of a prosthesis to ensure optimal eccentric occlusion is challenging without precisely replicating the patient's mandibular movements. During the CAD-CAM prosthesis delivery process, clinicians often need to make adjustments to the prosthesis to avoid occlusal interferences that may occur during lateral excursions. Recently, there have been developments in the field of mandibular motion tracking using optical devices. These approaches seek to incorporate an individual's functional movement into the research field of occlusal morphology. Aim This study aimed to assess the accuracy of digitally replicating mandibular movements to identify and correct occlusal interferences in monolithic CAD-CAM zirconia crowns. Methods An intraoral scanner (IOS) was used to capture complete arch maxillary and mandibular teeth and record buccal and lateral interocclusal records of maxillary first premolar abutment teeth of thirteen participants. For each patient, two monolithic zirconia crowns were fabricated following the standard digital workflow. The crowns were categorized based on the virtual method used for adjusting occlusal interferences into two groups: Group I, where occlusal interferences in CAD-CAM zirconia crowns were adjusted using buccal interocclusal records, and Group II, where adjustments were made using both buccal and lateral interocclusal records. After crown fabrication following the manufacturer's instructions, occlusion was analyzed using an electronic pressure analyzer. The mean, standard deviation and median values of the recorded data were measured. Paired t test and Wilcoxon Sign Rank test were executed for analyzing differences between groups (p value ≤ 0.05). Results Group I recorded higher maximum pressure at lateral mandibular movement with mean ± standard deviation value of 26.00 ± 4.95% than Group II with 20.62 ± 3.38%. Regarding pressure recorded at maximum intercuspation (MI) Group I showed higher results; 8.08 ± 1.50% compared to Group II with 7.23 ± 1.59% mean ± standard deviation value. The average value of crown volume for Group I was (160.36 ± 15.94) mm3, while for Group II was (157.63 ± 14.45) mm3. Conclusions The digital functionally generated path technique allows for identifying occlusal interferences and modifying CAD-CAM zirconia crown designs.